Relative Elevation Approach for Flood Susceptibility Assessment and Residential Zoning in Pallangga, Indonesia - Muh. Wahyu Apriliandi; Dwi Putro Tejo Baskoro; Wahyu Iskandar (Universitas Negeri Gorontalo, 2026)
Flood susceptibility assessment is essential for supporting land-use control and mitigation-oriented spatial planning in rapidly developing downstream areas. This study aimed to assess flood susceptibility in the Pallangga District, Gowa Regency, Indonesia, using a simplified GIS-based approach and evaluate its implications for residential zoning in the Regional Spatial Plan (RTRW). Four parameters were used: BU land density, distance from the river, relative elevation, and slope. BU land density was derived from Sentinel-2 L2A imagery using the spectral index rule-based classification approach, whereas relative elevation and slope were generated from DEMNAS data. Each parameter was scored and weighted based on expert judgment and then integrated using the weighted overlay method. The flood susceptibility index was classified into low-, moderate-, and high-risk classes using the natural breaks method and generalized using the minimum mapping unit approach. The results showed that moderate flood susceptibility dominated the Pallangga District, covering 2,965.0 ha (53.0 %) of the total area, followed by low susceptibility at 1,442.5 ha (25.7 %) and high susceptibility at 1,191.5 ha (21.3 %). High-risk areas were mainly concentrated in the northern part of the district, where low relative elevation, flat slopes, river proximity, and higher BU land density interact spatially. Overlay analysis with RTRW residential zoning indicated that 736.3 ha (38.5 %) of the planned residential areas were located within high-flood-susceptibility zones. These findings highlight the need to integrate flood susceptibility information into residential zoning evaluations, land-use control, and local flood mitigation planning.